Zim Ventures Management System - Ayani Chong Muhammad Amin Chong; Hamzah, Mohd Hamdi Irwan (Applied Information Technology And Computer Science, 2023)
Zim Ventures Enterprise is a company based in Plentong, Johor that still manually manages all relevant information such as project information and sub-contractor information. However, this manual method for maintaining all related information is time-consuming since project-related documents are kept manually. Therefore, a web-based management system is proposed to minimize the difficulties of tracking projects progression and management in Zim Ventures Enterprise. Meanwhile, the object-oriented approach was used to develop this project using a Waterfall model which includes requirement phase, design phase, development phase, testing phase and maintenance phase. The MySQL database is used in the design of this proposed system. PHP and HTML are the programming languages used. In general, the Zim Ventures Management System is designed to improve the efficiency and effectiveness in managing the data of Zim Ventures Enterprise.